Trends in cassava production - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Global cassava production is expected to show continued growth over the next five years with Africa leading the way. Five countries, Brazil, the Democratic Republic of the Congo, Indonesia, Nigeria and Thailand account for almost 70 per cent of the...